Adult muscle-derived stem cells engraft and differentiate into insulin-expressing cells in pancreatic islets of diabetic mice - Mitutsova, Violeta; Wai, Wendy Yeng Yeo; Davaze, Romain; Franckhauser, Celine; El-Habib, Hani; Abdullah, Syahril; Mollard, Patrice; Schaeffer, Marie; Fernandez, Anne; Lamb, Ned J. C. (BioMed Central, 2017)
BACKGROUND: Pancreatic beta cells are unique effectors in the control of glucose homeostasis and their deficiency results in impaired insulin production leading to severe diabetic diseases. Here, we investigated the potential of a population of nonadherent muscle-derived stem cells (MDSC) from adult mouse muscle to differentiate in vitro into beta cells when transplanted as undifferentiated stem cells in vivo to compensate for beta-cell deficiency. RESULTS: In vitro, cultured MDSC spontaneously differentiated into insulin-expressing islet-like cell clusters as revealed using MDSC from transgenic mice expressing GFP or mCherry under the control of an insulin promoter. Differentiated clusters of beta-like cells co-expressed insulin with the transcription factors Pdx1, Nkx2.2, Nkx6.1, and MafA, and secreted significant levels of insulin in response to glucose challenges. In vivo, undifferentiated MDSC injected into streptozotocin (STZ)-treated mice engrafted within 48 h specifically to damaged pancreatic islets and were shown to differentiate and express insulin 10-12 days after injection. In addition, injection of MDSC into hyperglycemic diabetic mice reduced their blood glucose levels for 2-4 weeks. CONCLUSION: These data show that MDSC are capable of differentiating into mature pancreatic beta islet-like cells, not only upon culture in vitro, but also in vivo after systemic injection in STZ-induced diabetic mouse models. Being nonteratogenic, MDSC can be used directly by systemic injection, and this potential reveals a promising alternative avenue in stem cell-based treatment of beta-cell deficiencies.